2021
DOI: 10.3390/hydrology8010015
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Response of Natural Mediterranean Watersheds to Forest Fires

Abstract: Fires are common in forested Mediterranean-climate watersheds. Forest fires cause abrupt land use/cover (LULC) changes affecting soil properties and hydrological processes within and across watersheds. A major forest fire in Attica, Greece, that affected the Lykorrema stream experimental watershed provided the opportunity for an in-depth study of the impact of forest fires on the hydrological balance of natural Mediterranean watersheds. To this end, detailed hydrometeorological data recorded for five years bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 75 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…According to [13], the runoff rate increased three times and the soil loss was doubled after the forest fire in Spain. Previous research [17,18] showed that for the hillslope sediment yield balance, three to five years are usually required, while others [147] denoted the increase in sediment yield before and after the wildfire of 2009 in the Penteli region (Lykorrema watershed), where a mean pre-fire value of 0.02 t/ha/yr was replaced by a mean post-fire value of 0.13 t/ha/yr (for 2009-2014 estimation). The results displayed in this article are in agreement with previous researchers, showing that, in the Mediterranean conditions, the maximum soil erosion susceptibility is recorded within 4-6 months after the fire [148,149], as depicted in the Ilioupoli test site.…”
Section: Discussionmentioning
confidence: 99%
“…According to [13], the runoff rate increased three times and the soil loss was doubled after the forest fire in Spain. Previous research [17,18] showed that for the hillslope sediment yield balance, three to five years are usually required, while others [147] denoted the increase in sediment yield before and after the wildfire of 2009 in the Penteli region (Lykorrema watershed), where a mean pre-fire value of 0.02 t/ha/yr was replaced by a mean post-fire value of 0.13 t/ha/yr (for 2009-2014 estimation). The results displayed in this article are in agreement with previous researchers, showing that, in the Mediterranean conditions, the maximum soil erosion susceptibility is recorded within 4-6 months after the fire [148,149], as depicted in the Ilioupoli test site.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the scientific literature describes a wide spectrum of empirical formulations [49][50][51], in this integrated approach, the Natural Resources Conservation Service-Soil Conservation Service (NRCS-SCS) method [41,52] was used. This method, described by Equation (7), directly depends on the length of the main water stream L (km), while it is inversely proportional to the average slope of the watershed (m m −1 ) and CN:…”
Section: Rainfall-runoff Simulation Strategymentioning
confidence: 99%
“…The ability to survive and re-sprout depends on tree height, scorch and char heights, tree species, age, stem and bark thickness, and fire intensity and residence time. In the hydrological cycle, this natural process leads to a reduction in evapotranspiration fluxes, leaf rainfall interception and tree suction capacity [7]. High temperatures can vaporize soil organic matter and generate a thin hydrophobic layer (from 1 to 7 cm), which strongly reduces soil infiltration capacity [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, wildfires, i.e., extreme free-burning fires, have a significant impact on ecosystems' natural balance [2,3]. Fires affect ecosystems, causing change in vegetation patterns, soil properties, and hydrological processes, consequently altering the watershed conditions and water quality and hence posing a threat to water supply sources [4][5][6][7][8]. They also have a devastating impact on property, infrastructure, and populations' health and lives.…”
Section: Introductionmentioning
confidence: 99%